Measurements of the muon shower content at the Pierre Auger Observatory - Yushkov A. (EPJ Web of Conferences, 2013)
Several methods for estimating the muonic part of the signal observed in the surface Cherenkov detectors have been developed within the Pierre Auger Collaboration in the recent years. The muon shower content, derived from data with these methods, is found to be significantly larger in comparison with predictions of QGSJET II interaction model.